Five-year follow-up of first-episode depression treated with psychodynamic psychotherapy or antidepressants. (May 2019) - Rosso, Gianluca; Aragno, Elena; Cuomo, Alessandro; Fagiolini, Andrea; Di Salvo, Gabriele; Maina, Giuseppe
Highlights: 5-year retrospective follow-up on 93 remitters from a first major depressive episode. Less depressive recurrences in remitters to brief dynamic therapy than in remitters to antidepressants. Significantly higher rates of hypomanic/manic episodes in remitters to antidepressants. Abstract: Short-term psychodynamic psychotherapy (STPP) both combined with medication and alone has been shown to be effective in major depressive disorder (MDD). However, few studies compared STTP and pharmacotherapy in monotherapy during acute phase and there is lack of data concerning the prevention of recurrences. The aim of this retrospective study was to evaluate the clinical course of patients who achieved remission from their first life-time major depressive episode after treatment with antidepressant (AD) therapy or brief dynamic therapy (BDT), a specific type of STPP, examining the recurrence rates during a 5-year treatment-free period. The analysis was conducted on 93 subjects (remitters to BDT n  = 46; remitters to AD n  = 47). Treatment with BDT was associated with a significantly higher proportion of patients without depressive recurrences during the observation period. Among patients who were remitters to BDT, 71.7% did not experience depressive recurrences at the end of the observation period, compared to 46.8% of those treated with pharmacotherapy. BDT may be more effective than AD pharmacotherapy in improving the long-term outcome of patients with a first major depressive episode; further studies comparing STPP and AD in terms of efficacy and cost-effectiveness are needed.